2010
DOI: 10.2353/ajpath.2010.100322
|View full text |Cite
|
Sign up to set email alerts
|

Novel Lipid Mediators and Resolution Mechanisms in Acute Inflammation

Abstract: Because inflammation is appreciated as a unifying basis of many widely occurring diseases, the mechanisms involved in its natural resolution are of considerable interest. Using contained, self-limited inflammatory exudates and a systems approach, novel lipid-derived mediators and pathways were uncovered in the resolution of inflammatory exudates. These new families of local mediators control both the duration and magnitude of acute inflammation as well as the return of the site to homeostasis in the process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
354
0
7

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(365 citation statements)
references
References 149 publications
(249 reference statements)
4
354
0
7
Order By: Relevance
“…An important process in inflammation resolution is the dampening of proinflammatory molecules in a manner that does not compromise host defense (2). Thus, it is essential to understand at a molecular-cellular level how this critical process is achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important process in inflammation resolution is the dampening of proinflammatory molecules in a manner that does not compromise host defense (2). Thus, it is essential to understand at a molecular-cellular level how this critical process is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, uncovering mechanisms to suppress inflammation and enhance resolution is of immense interest (2)(3)(4)(5). Resolution is orchestrated in part by specialized proresolving mediators (SPMs), including lipoxins, resolvins, protectins, and maresins (2), and by protein and peptide mediators (6).…”
mentioning
confidence: 99%
“…DHA-derived resolvins act as a cytoprotective mechanism against oxidant injury 6,7 and the pro-resolving mediators, eg, lipoxin A4 and resolvins, can return the permeability/edema to normal. 8 Previous studies have showed that RvD1 displays potent anti-oxidative stress, 9 anti-inflammation, and pro-resolving actions that have been demonstrated in mouse models of ALI. [10][11][12] Though they have been observed that RvD1 can reduce pulmonary edema induced by lipopolysaccharide (LPS), the effects of RvD1 on TJ protein remain elusive.…”
mentioning
confidence: 98%
“…Ideally, this response is self-limited and leads to clearance of pathogens, cellular debris, and inflammatory mediators (1,2). However, an excessive inflammatory response impairs resolution and leads to chronic inflammation and subsequent tissue damage (2)(3)(4). Increasing evidence suggests that excessive inflammation and impaired resolution play central roles in several prevalent diseases including cardiovascular, metabolic, and neurodegenerative diseases (5).…”
mentioning
confidence: 99%